14-3-3σ Contributes to Radioresistance by Regulating DNA Repair and Cell Cycle via PARP1 and CHK2 - Chen, Yifan (Mol Cancer Res, 2017)
14-3-3σ has been implicated in the development of chemo and radiation resistance and in poor prognosis of multiple human cancers. While it has been postulated that 14-3-3σ contributes to these resistances via inhibiting apoptosis and arresting cells in G2/M phase of the cell cycle, the molecular basis of this regulation is currently unknown. In this study, we tested the hypothesis that 14-3-3σ causes resistance to DNA-damaging treatments by enhancing DNA repair in cells arrested in G2/M phase following DNA-damaging treatments. We showed that 14-3-3σ contributed to ionizing radiation (IR) resistance by arresting cancer cells in G2/M phase following IR and by increasing non-homologous end joining (NHEJ) repair of the IR-induced DNA double strand breaks (DSBs). The increased NHEJ repair activity was due to 14-3-3σ-mediated up-regulation of Poly(ADP-ribose) polymerase 1 (PARP1) expression that promoted the recruitment of DNA-PKcs to the DNA damage sites for repair of DSBs. On the other hand, the increased G2/M arrest following IR was due to 14-3-3σ-induced Chk2 expression. IMPLICATIONS: These findings reveal an important molecular basis of 14-3-3σ function in cancer cell resistance to chemo/radiation therapy and in poor prognosis of human cancers.